2013
DOI: 10.1063/1.4829464
|View full text |Cite
|
Sign up to set email alerts
|

Metal to semiconductor transition in metallic transition metal dichalcogenides

Abstract: Stability, structural, and magnetic phase diagrams of ternary ferromagnetic 3d-transition-metal clusters with five and six atoms J. Chem. Phys. 134, 054101 (2011); 10.1063/1.3533954 Thickness dependence of ferromagnetic-and metal-insulator transition in thin EuO filmsWe report on tuning the electronic and magnetic properties of metallic transition metal dichalcogenides (mTMDCs) by 2D to 1D size confinement. The stability of the mTMDC monolayers and nanoribbons is demonstrated by the larger binding energy compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 44 publications
(39 reference statements)
0
19
0
Order By: Relevance
“…A sequence that resembles the targeted compounds is evaporated onto a silicon substrate with the correct stoichiometric and thickness ratio of the final compounds. (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) were synthesized using similar conditions. For each sample (([SnSe] 1.16 ) m (NbSe 2 ) 2 ), m layers of SnSe (m = 1-20) and two layers of NbSe 2 were repeatedly deposited until a thickness of ~ 50 nm was reached.…”
Section: Synthesis and Structurementioning
confidence: 99%
See 1 more Smart Citation
“…A sequence that resembles the targeted compounds is evaporated onto a silicon substrate with the correct stoichiometric and thickness ratio of the final compounds. (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) were synthesized using similar conditions. For each sample (([SnSe] 1.16 ) m (NbSe 2 ) 2 ), m layers of SnSe (m = 1-20) and two layers of NbSe 2 were repeatedly deposited until a thickness of ~ 50 nm was reached.…”
Section: Synthesis and Structurementioning
confidence: 99%
“…2,10,11 The change in dimensionality from three to two has been shown to lead to changes in interlayer coupling, degree of quantum confinement and electronic structures. 13,14 There are also reports where ultra-thin films maintain bulk properties, for example the charge density wave (CDW) transition is still observed in nanosheets of metallic VSe 2 . NbX 2 and TaX 2 , which show a CDW and a superconducting transition in bulk, have been reported to exhibit semiconducting properties as nanosheets.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the spin-valve effect was evidenced in experiments performed for a monolayer MoS 2 acting as a nonmagnetic spacer in NiFe/MoS 2 /NiFe heterostructures [31] and a similar spin-dependent transport behavior was revealed for Fe 3 O 4 /MoS 2 /Fe 3 O 4 magnetic tunnel junctions [32]. From a theoretical point of view, several studies focused especially on the electronic properties of the intrinsic magnetic VS 2 and VSe 2 monolayers [33,34], in TMD nanoribbons [35,36], in hydrogenated [37] and fluorinated [38] single TMD layers, and in TMD monolayers doped with transition metal atoms [39][40][41] or strain-induced ones [42][43][44]. On the other hand, less attention was focused on the properties of TMDs on magnetic substrates [45][46][47][48][49][50] that can serve, for instance, as electrodes in spintronic devices [51].…”
Section: Introductionmentioning
confidence: 64%
“…However, great efforts have been made to fabricate these materials on a large scale because of their fundamental properties, including electrical, optical, mechanical, thermal and chemical. [145][146][147][148] Interestingly, Staley et al observed superconductivity in two molecular layer NbSe 2 flakes. 145 An onset superconducting transition temperature (T c ) was up to 2.5 K. Similar phenomena were achieved in a few molecular layer NbSe 2 flakes field-effect transistors.…”
Section: Mixer Switch Modulator and Resonatormentioning
confidence: 96%